Subjective well-being and income: A compromise between Easterlin paradox and its critiques - Rusen Yasar (Kiel Institute for the World Economy (IfW), 2017)
Despite rising popularity of subjective well-being (SWB) as a proxy for utility, its relationship with income is still unresolved. Against the background of debates around the 'Easterlin paradox', this paper seeks a compromise between two positions: one that insists on individual relative income, and one that finds similarity between individual and aggregate levels. Proposing a model which puts the emphasis on the interaction between individual and aggregate-level factors, it argues that the effect of relative income on SWB varies across countries as a function of average income, in addition to a relatively small direct effect of the latter, in partial agreement with the two major positions. The model is tested cross-sectionally on the data from the latest wave of World Values Survey. The results from hierarchical mixed-effect models confirm the main argument. But further examination reveals that there is still unaccounted variation especially in middle-income economies.
Keywords: D31; C31; 330; subjective well-being; Easterlin paradox; relative income; national income